Handbook of research on geriatric health, treatment, and care - Vijaya Prasad, Barre, 1981-; Akbar, Shamsi, 1985- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2018)
"This book examines research focused on new methodologies for identifying and diagnosing the epidemiological factors contributing for geriatric health issues and older adults in the community. It discusses research related to psychopharmacological inventions and the care of older adults, disability due to multiple health complications for older adults and acts to protect the rights of older adults"--Provided by publisher.